1998
DOI: 10.1128/iai.66.3.987-993.1998
|View full text |Cite
|
Sign up to set email alerts
|

Phase Variation of Hemoglobin Utilization in Neisseria gonorrhoeae

Abstract: Most Neisseria gonorrhoeae isolates are unable to use human hemoglobin as the sole source of iron for growth (Hgb−), but a minor population is able to do so (Hgb+). This minor population grows luxuriously on hemoglobin, expresses two outer membrane proteins of 42 kDa (HpuA) and 89 kDa (HpuB), and binds hemoglobin under iron-stressed conditions. In addition to the previously reported HpuB, we identified and characterized HpuA, which is encoded by the gene hpuA, located immediately upstream of hpuB. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 48 publications
3
64
0
Order By: Relevance
“…Thus, HpuB alone may bind free Hb, albeit with a very low affinity, as significant binding of [ 125 I]-Hb was not detected in liquid phase binding assays. Overall, our findings are consistent with the results of Chen et al (1998), who showed that an HpuA -B + strain of N. gonorrhoeae showed impaired, but detectable, Hb binding in a solid phase dot-blot assay. Nonetheless, although HpuB itself may interact with Hb, optimal binding of this ligand and acquisition of haem-Fe by HpuAB of both pathogenic Neisseria species require both receptor proteins acting in concert.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, HpuB alone may bind free Hb, albeit with a very low affinity, as significant binding of [ 125 I]-Hb was not detected in liquid phase binding assays. Overall, our findings are consistent with the results of Chen et al (1998), who showed that an HpuA -B + strain of N. gonorrhoeae showed impaired, but detectable, Hb binding in a solid phase dot-blot assay. Nonetheless, although HpuB itself may interact with Hb, optimal binding of this ligand and acquisition of haem-Fe by HpuAB of both pathogenic Neisseria species require both receptor proteins acting in concert.…”
Section: Discussionsupporting
confidence: 92%
“…In the structurally analogous Tf and Lf receptors, the lipoprotein is surface exposed and is not required for receptor function, playing an accessory role in ligand specificity and binding (Cornelissen and Sparling, 1996;Bonnah and Schryvers, 1998;Lewis et al, 1998b;Pettersson et al, 1998). In contrast, isogenic single mutants of meningococcal and gonococcal HpuAB suggested that both receptor components are required for the binding and utilization of Hb or HbHp (Chen et al, 1998;Lewis et al, 1999). The precise roles of HpuA and HpuB in this process have not yet been described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that gonococci primarily use the HpuAB receptor because of a premature stop codon in the hmbR gene (Chen et al, 1996;Stojiljkovic et al, 1996), perhaps reflecting the prevalence of Hb-Hp as an iron source under these conditions. Phase variation of expression of HpuAB, resulting from slipped-strand mispairing in a poly(G) tract in the hpuA gene (Chen et al, 1998), also seems appropriate considering the episodic nature of the supply of haem iron.…”
Section: Iron Acquisition From Haem and Haemoglobinmentioning
confidence: 99%
“…It is unclear what advantage might be gained by the regulation of hemoglobin binding proteins by both phase variation and heme levels. It has been proposed that phase variation of a hemoglobin binding protein in gonococci might enable efficient utilization of menstrual hemoglobin (2). Such a mechanism may modulate expression of proteins in different host sites, depending on the prevalent heme source, enabling the infecting organism to adapt to specific host microenvironments.…”
Section: Fig 3 Phase Variation Between a Non-lacz-expressing Phenotmentioning
confidence: 99%